Standardization Parameters of few India herbal drugs used in the treatment of gynecological disorders - Shriwas, Shweta; Choukse, Raju; Dwivedi, Sumeet (Journal of Drug Delivery and Therapeutics, 2019)
Gynecological disorders are very common among Indian women and are more prone in rural areas as compared with urban due to various issue among with un-hygienic conditions are at the top. As per Ayurvedic literature there are several plants used to cure women disorders, though there proper documentation and validation need to be established for quality and purity of herbal drugs. The present work aims to investigate the acute toxicity profile of few India medicinal plants. In this present study standardization parameters of Achyranthes aspera Linn. (Roots) ASR, Clitoria ternatea Linn. (Roots) CTR, Ipomea cairica Linn. (Leaves) ICL and Plumeria pudica Jacq. (Leaves) PPL were investigated. The present investigation shows the results of morphological features and physicochemical evaluation of selected herbal drugs.Keywords: Herbal drugs, Standardization parameters, Quality, gynecological disorders